Smart village concept in Indonesia: ICT as determining factor - Anindya Puteri Eka Susilowati; Rini Rachmawati; R. Rijanta (Heliyon)
Village development in Indonesia has become the national development agenda prioritized in conjunction with the enactment of the Village Law in 2014. Village development through smart village is considered relevant to the current era's progress and rapid technological advancements. Smart village is often defined as the concept of village development based on the utilization of information and communication technology (ICT). This research aims to identify the locations of smart village and analyze the role of ICT as determining factor for the smart village concept in Indonesia. The data on smart village locations are collected from the regulations of the Ministry of Village and literature obtained through internet browsing. The research was conducted using a quantitative descriptive approach and supported by spatial analysis. The exploration of determining factors for the smart village concept involves 12 variables sourced from the Village Potential data in 2021 and analyzed statistically using factor analysis. The results indicate that there are 1.424 villages developed as smart village until 2023 and their locations are spread across 32 provinces on all islands in Indonesia. The results show that ICT is one of the determining factors in the smart village concept in Indonesia through the utilization of village information systems in government (explained 15,972 % variance), community interest in ICT (explained 10,628 % variance), and the availability of communication access (explained 8509 % variance). However, ICT is not the only determining factor, but there are also internal village factors: community participation (explained 11,299 % variance) and leadership (explained 9137 % variance). From these findings, it implies that smart village development policies need to pay attention to the conditions of society as the subject and object of development, supported by the government's ability to provide adequate infrastructure. This research is a pioneer and provides real innovation in smart village studies so that it can be a reference for similar studies in the future, both in smaller areas (provinces/regencies), or countries with conditions similar to Indonesia.